ANALISIS PEMANFAATAN GOOGLE CLASSROOM SEBAGAI KELAS MAYA DALAM PEMBELAJARAN SELAMA PANDEMI COVID-19 DITINJAU DARI BERBAGAI PERSPEKTIF - Novi Ayu Kristiana Dewi; Bernaditha Herindri Samodera Utami; Suhono Suhono (Universitas Muhammadiyah Metro, 2021)
The purpose of this study is to reveal how the implementation of Google Classroom as a virtual classroom learning media during the covid-19 pandemic so known benefits and weaknesses by various respondents . This research is a descriptive qualitative research with data collection through closed and open questionnaires given to 89 respondents randomly consisting of lecturers, teachers, and students in Lampung Province. The results of this study can be concluded that lecturers and students have implemented google classroom before the covid-19 pandemic as a support for blended learning activities so that they are used to doing online learning during pandemic. Meanwhile, teachers and students have only implemented Google Classroom since the Covid-19 pandemic, although Google Classroom provides many benefits as a learning medium, but there are still some who are not used to it and are constrained by the internet network.Keywords: google classroom, vistual classroom, learning during the covid-19 pandemic